Differences in Mental Toughness in Mountain Climbers in terms of Gender: Perbedaan Mental Toughness pada Pendaki Gunung Ditinjau dari Jenis Kelamin - Saputro, Yofi Catur; Affandi, Ghozali Rusyid (Psikologia : Jurnal Psikologi, 2022)
This research conducted by the importance of paying attention to the level of mental toughness in mountain climbers. To overcome the difficulties and obstacles of situation, mental toughness help the mountain climbers to address and solve the problem properly, which will affect the success of mountaineering. One of the factors that affect mental toughness is gender. This study aimed to determine the differences of mental toughness in mountain climbers’ in terms of gender. This research is a type of quantitative research with comparative approach. The variable in this study are: Mental toughness as dependent variable and gender as independent variable. The sample of this research was 108 members of Nature Lovers Student Organization Sidoarjo (Students for Nature Lovers' Sidoarjo), consisting of 54 male and 54 female. Sampling technique was done by using accidental sampling. The measuring instrument used to collect data is mental toughness scale which was compiled based on the mental toughness dimension proposed by Guciardi, et al. The data analysis method was carried out by independent sample T-test using JASP program version 0.14.0.0 for windows. The result showed that there were differences in mental toughness between male and female mountaineering students. It showed a significance result of 0.033 (p<0.05), which means that hypothesis in this study can be accepted.